2016
DOI: 10.1016/j.rfe.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Are Smart Beta strategies suitable for hedge fund portfolios?

Abstract: In the equity context different Smart Beta strategies (such as the equally weighted, global minimum variance, equal risk contribution and maximum diversified ratio) have been proposed as alternatives to the capweighted index. These new approaches have attracted the attention of equity managers as different empirical analyses demonstrate the superiority of these strategies with respect to cap-weighted and to strategies that consider only mean and variance. In this paper we focus our attention to hedge fund inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…six months). The effect of n is in line with the results derived in [15]. However, also for this dataset, the network-based approaches over-perform the GMV strategy, in terms of both average performance and risk-adjusted measures.…”
Section: Alternative Datasets and Different Rolling Windowssupporting
confidence: 86%
See 1 more Smart Citation
“…six months). The effect of n is in line with the results derived in [15]. However, also for this dataset, the network-based approaches over-perform the GMV strategy, in terms of both average performance and risk-adjusted measures.…”
Section: Alternative Datasets and Different Rolling Windowssupporting
confidence: 86%
“…In the majority of the cases, papers [20,24]. Empirical analyses have shown that the use of improved estimators for moments and co-moments leads to higher out-of-sample performance compared to the sample estimation, see among others [15]. both long-term performances and risk-adjusted measures tend to provide the best behaviour at least for one of the network-based approaches.…”
mentioning
confidence: 99%
“…To overcome these main drawbacks, several variations and extensions of the original methodology have been proposed in the literature. In [20], a higher out-of-sample performance is derived by imposing specific constraints, and these results have been further confirmed in [4,18]. Alternative approaches deal with the problem of optimal portfolio choice by employing a Bayesian methodology to estimate unknown mean-variance parameters reducing the estimation errors.…”
Section: Introductionmentioning
confidence: 68%
“…The authors in [26] propose the shrinkage estimator toward the constant correlation, while in [31] this approach has been extended to higher moments such as skewness and kurtosis. Empirical analyses have shown that the use of shrinkage estimators for the mean-variance parameters often improves the out-of-sample performance (see [18,19]).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, the in-sample and the out-of-sample windows involve 104 and four observations respectively. These parameter choices are typical settings for portfolio selection problems (Hitaj & Zambruno, 2016).…”
Section: Methodsmentioning
confidence: 99%